First Webinar on Language Learning & Teaching – WeLLT 2020 - Hanisah, Kasbon (Pusat Bahasa Moden (PBM), 2021)
In addressing the present issue in language learning and teaching in the era Covid-19, the Centre for Modern Languages, Universiti Malaysia Pahang (UMP) in collaboration with Universitas Ahmad Dahlan hosted a Webinar on Language Learning and Teaching (WeLLT) 2020 on 28 October 2020. This virtual session was organized in conjunction with International on Language Learning and Teaching (ICoLLT) that will be held in 2021.